2022
DOI: 10.3390/ijerph19105879
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Environmental Innovation Strategy on Green Competitiveness: Evidence from China

Abstract: Environmental issues are a significant field in both research and practice. Manufacturing enterprises are adopting sustainable initiatives to achieve efficient resource usage, emissions reduction, energy utilization reduction, and improve waste management. Therefore, drawing on ecological modernization theory (EMT) and knowledge-based theory (KBT), this study proposes a comprehensive framework for the relationships among environmental innovation strategy (EIS), green knowledge sharing (GKS), organizational gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 76 publications
0
4
0
1
Order By: Relevance
“…Literature Achieving competitive advantages through the introduction of green technologies (Kuhn et al, 2022;Lenox, 2021;Wang et al, 2022) The relationship between energy production and consumption on the one hand, and carbon emissions on the other (Dalla Longa et al, 2022;Natali et al, 2021;Pandey et al, 2022) Increasing energy efficiency as a key area of national economies' decarbonisation (Mier et al, 2020;Obrist et al, 2022;Pakhomova et al, 2021) The relationship between investments in renewable energy sources and CO2 emissions (Acheampong et al, 2019;Ikram et al, 2020;Mehmood et al, 2022) The Impact of government initiatives to promote decarbonisation on economic performance (Al Mamun et al, 2022;Rissman et al, 2020;Stephenson et al, 2021) Managing companies in the context of "carbon tax" introduction (Dixit et al, 2022;Domon et al, 2022;Reaños et al, 2022) Rebound effect of energy efficiency (Chen et al, 2021;Baležentis et al, 2021;Berner et al, 2022) Source: authors.…”
Section: Research Areamentioning
confidence: 99%
“…Literature Achieving competitive advantages through the introduction of green technologies (Kuhn et al, 2022;Lenox, 2021;Wang et al, 2022) The relationship between energy production and consumption on the one hand, and carbon emissions on the other (Dalla Longa et al, 2022;Natali et al, 2021;Pandey et al, 2022) Increasing energy efficiency as a key area of national economies' decarbonisation (Mier et al, 2020;Obrist et al, 2022;Pakhomova et al, 2021) The relationship between investments in renewable energy sources and CO2 emissions (Acheampong et al, 2019;Ikram et al, 2020;Mehmood et al, 2022) The Impact of government initiatives to promote decarbonisation on economic performance (Al Mamun et al, 2022;Rissman et al, 2020;Stephenson et al, 2021) Managing companies in the context of "carbon tax" introduction (Dixit et al, 2022;Domon et al, 2022;Reaños et al, 2022) Rebound effect of energy efficiency (Chen et al, 2021;Baležentis et al, 2021;Berner et al, 2022) Source: authors.…”
Section: Research Areamentioning
confidence: 99%
“…1. Основные направления исследований по решению проблем декарбонизации Направление Литература Возможности достижения конкурентных преимуществ за счет внедрения экологически чистых технологий (Kuhn et al, 2022;Lenox, 2021;Wang et al, 2022) Исследования связи между производством и потреблением энергии, с одной стороны, и эмиссией углеродных соединений -с другой (Dalla Longa et al, 2022;Natali et al, 2021;Pandey et al, 2022) Повышение энергетической эффективности как ключевое направление декарбонизации национальных экономик (Mier et al, 2020;Obrist et al, 2022; Пахомова и др., 2021) Оценка корреляции между инвестициями в возобновляемые источники энергии и эмиссией СO2 (Acheampong et al, 2019;Ikram et al, 2020;Mehmood et al, 2022) Влияние государственного стимулирования процессов декарбонизации на показатели экономического развития (Al Mamun et al, 2022;Rissman et al, 2020;Stephenson et al, 2021) Управление деятельностью компаний в условиях введения «углеродного налога» (Dixit et al, 2022;Domon et al, 2022;Reaños et al, 2022) Рикошетный эффект (rebound effect) энергоэффективности (Chen et al, 2021;Baležentis et al, 2021;Berner et al, 2022) Источник: составлено авторами.…”
Section: методологияunclassified
“…Other scholars have evaluated the development level of the green competitiveness of municipalities based on four dimensions [12], namely economic green development, social green development, resource green development, and environmental green development, or three dimensions [13], namely green economy, green investment, green utilization, and green security. In addition, Wang et al (2022) constructed a comprehensive evaluation index system for green competitiveness in rural China based on the "green growth-green wealth-green welfare" framework [14]. (3) On the spatio-temporal patterns of green competitiveness.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies show that China's regional green competitiveness continues to improve, with the green competitiveness of the eastern region being much higher than that of the other regions, and the regional differences are characterized first by an increase and then a decrease; the coupling coordination degree of China's regional green competitiveness system exhibits significant spatial dependence, forming a high-coupling coordination degree agglomeration with Shanghai as the center spreading to the south and a low-coupling coordination degree agglomeration with Qinghai as the center spreading to the east [11]. Wang et al (2022) analyzed the spatial and temporal characteristics and drivers of China's rural green competitiveness through spatial autocorrelation (SA) analysis and GeoDetector and found that China's rural green development presents a spatial differentiation feature that is high in the eastern region and low in the central and western regions [14]. Ma et al (2023) analyzed regional differences in China's green competitiveness through methods such as coefficient of variation analysis and found that the coefficient of variation in green competitiveness of China's 30 provinces and the eastern, central, and western regions show an inverted U-shape trend of first increasing and then decreasing [19].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation